(untitled) (Research, Society and Development, 2023)
The search for aesthetic procedures has increased due to several factors in modern society, leading people to seek improvements through non-invasive procedures, such as orofacial harmonization (HOF) performed by dentists (CD). Hyaluronic Acid (HA) is currently considered one of the best fillers, since it is a substance naturally present in human skin, although its amount decreases over the years. Filling with HA can provide positive results, softening aging lines and improving facial contour. However, it is important to highlight the relationship between COVID-19 and the use of dermal fillers. Based on a narrative review and analysis of data available in the literature, it was concluded that COVID-19 may increase the risk of developing a rare but potentially serious complication called Persistent Intermittent Delayed Edema (IPTE) after the use of dermal fillers. Recent studies suggest that the virus can cause systemic inflammation and changes in blood clotting, which increases the risk of complications after the application of fillers. Therefore, it is critical that healthcare professionals are aware of the potential risks and take precautions to minimize patient exposure. It is also necessary to carefully assess the patients’ medical history prior to the dermal filler procedure in order to identify possible risk factors for the development of ETIP. The objective of this research is, through a narrative review of the literature about the relationship between COVID-19 and the use of dermal fillers, especially in the HOF specialty.